2015
DOI: 10.3126/jpn.v5i9.13785
|View full text |Cite
|
Sign up to set email alerts
|

p53 Expression in Oral cancer: A study of 50 cases

Abstract: Background: Oral cancer is the sixth most common cancer in the world. P53 mutations are associated with the development of oral squamous cell carcinomas. This study is to determine the presence of p53 oncogene expression in cases of oral malignant, premalignant and benign lesions and to show association of p53 oncogene and lymph node enlargement in malignant lesion. Materials and methods:Four to five micron-thick sections of formalin fixed, paraffin embedded biopsy material from various intra-oral sites of 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…In the present study p53 immunoexpression was noted in 62.1% of cases. The present study which was similar to the observations by Ghanghoria S et al 29 Umaswaminathan et al 30 Nighat Ara et al 23 where p53 expression was 63%,65%and 67% respectively, but expression of p53 was 20% higher in Nishat Sultana et al 31 where it was seen in 80% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study p53 immunoexpression was noted in 62.1% of cases. The present study which was similar to the observations by Ghanghoria S et al 29 Umaswaminathan et al 30 Nighat Ara et al 23 where p53 expression was 63%,65%and 67% respectively, but expression of p53 was 20% higher in Nishat Sultana et al 31 where it was seen in 80% of cases.…”
Section: Discussionsupporting
confidence: 92%
“…The present study observed a statistically significant relation between p53 staining intensity and p53 protein expression in tissue samples of OSCC. These findings are in obedience with the findings noted by Ara et al, and Azizi et al, 23,26 Among OSCC lesions, a statistically insignificant relation was observed between tissue p53 immunoreactivity and WHO OSCC grading system, age, gender, tobacco usage history, type of tobacco product consumed frequency of tobacco use per day, and duration of tobacco use in years. These findings are in obedience with the observations reported by Bhattacharya et al 27 However, a study done by Gatto et al, revealed a statistically significant relation between p53 immunoreactivity and histological grades and tobacco and betel quid habits and insignificant relation with age, gender of OSCC lesion.…”
Section: 25supporting
confidence: 83%
“…On chromosome 17p 13.1 of humans, the p53 gene is located which encodes a 53-kDa, 393 AA, and nuclear phosphoproteins known for cell proliferation and regulation of cell growth [ 30 ]. Three hundred ninety-three amino acids of the human p53 protein contains four major functional domains.…”
Section: Resultsmentioning
confidence: 99%